Synthesis method of spherical hydroxyapatite with controllable particle size
By dissolving calcium salts and carbonates in water/ethylene glycol solution, and preparing spherical HAPs by hydrothermal reaction and mechanical stirring methods, the problem of inability to customize particle size in the prior art is solved, and the particle size controllable of spherical HAPs is achieved and regular morphology improve the flexibility and economic benefits of the process.
Patent Information
- Application Number
- CN202411446670.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art cannot customize the particle size of spherical hydroxyapatite, which limits its application range.
Dissolve calcium salts and carbonates in water/ethylene glycol solution containing morphological control agents and particle size control agents, and synthesize spherical CaCO3 by hydrothermal reaction and mechanical stirring, and then react with phosphate to prepare spherical HAP by changing particle size Control the amount of agent added and hydrothermal conditions to control the particle size of HAP.
The controllable modulation of the particle size of spherical HAP is achieved between 300-1600 nm, ensuring that the product is regular and dispersible in a good manner, flexible process and significant social and economic benefits.
Smart Images

Figure CN119284849A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic functional materials, and in particular relates to a method for synthesizing spherical hydroxyapatite with controllable particle size. Background Art
[0002] Hydroxyapatite (HAP) is a calcium phosphate biomaterial with a chemical formula of Ca 10 (PO 4 ) 6 (OH) 2 , widely exists in nature and organisms, has good biocompatibility, and is widely used in the medical industry, pharmaceutical industry and chemical industry. HAP has a variety of morphologies, such as spherical, needle-shaped, short rod-shaped, and fibrous. Among them, spherical HAP has attracted widespread attention due to its advantages such as good affinity, large specific surface area, uniform pore distribution, high mechanical strength, good fluidity, and high packing density. In the field of bone repair, spherical HAP, as a 3D printing material, can ensure that personalized repair scaffolds have high structural stability and biocompatibility, thereby improving the repair effect and alleviating the pain of patients; in gas sensing, spherical HAP can be used as a sensitive material for detecting and identifying different types of gas molecules; in the field of catalysis, spherical HAP can be used as a catalyst carrier to improve the efficiency and selectivity of catalytic reactions; in the field of ion exchange, the ion exchange performance of spherical HAP makes it an effective material for treating wastewater and purifying water quality; and in terms of drug sustained release, spherical HAP can achieve slow release and directional delivery of drugs, thereby improving the effect and safety of drug treatment.
[0003] The preparation methods of HAP are mainly divided into dry solid phase synthesis method and wet aqueous phase synthesis method. Wet aqueous phase synthesis of HAP is the most widely used method at present because of its simple operation and more uniform HAP obtained, including chemical precipitation method, hydrothermal method, template method, etc. The template method uses a substance with a specific morphology and structure as a template for synthesizing HAP. Patent CN110078037B uses carbon quantum dots as a template, phosphate buffer solution as a phosphorus source, anhydrous calcium chloride as a calcium source, and Tween 80 as a surfactant. The reaction is stirred in a water bath at 80°C, and then centrifuged and dried. The HAP nanoparticles with a spherical morphology are calcined to obtain a particle size range of 100-250 nm. Patent CN111115603B uses anhydrous sodium carbonate and calcium chloride as raw materials, which are dissolved in water to make a solution, and calcium carbonate (CaCO 3 ), and then CaCO 3 Spherical HAP containing strontium was synthesized hydrothermally by using template, strontium chloride and phosphate at pH 5-9, with a particle size of about 3 μm. The particle size of spherical HAP obtained by the above two preparation methods cannot be customized, and its application range is limited. Summary of the invention
[0004] In view of the problems in the prior art, the present invention discloses a method for synthesizing spherical hydroxyapatite with controllable particle size. Not only can spherical HAP with regular morphology and good dispersibility be synthesized, but also the particle size of HAP can be customized. In the present invention, calcium salt and carbonate are dissolved in a water / ethylene glycol solution containing a morphology control agent and a particle size control agent to synthesize spherical CaCO 3 , template CaCO 3 The spherical HAP is synthesized by hydrothermal reaction with phosphorus source under alkaline conditions and mechanical stirring, and the particle size of the spherical HAP is controlled by changing the amount of particle size control agent added. The specific steps are: (1) Mixing water and ethylene glycol in proportion, and dissolving a morphology control agent and a particle size control agent therein to form a water / ethylene glycol system; (2) The water / ethylene glycol system obtained in step (1) is divided into two parts, and a soluble calcium salt is dissolved therein to form a calcium salt solution, and a soluble carbonate is dissolved therein to form a carbonate solution.
[0005] (3) Stir and heat the carbonate solution obtained in step (2), pump the calcium salt solution at the same temperature into it, react for a period of time, centrifuge, wash, and dry to obtain spherical CaCO 3 ; (4) Dissolving soluble phosphate in water to obtain a phosphate solution, adjusting the pH to alkaline, and mixing the spherical CaCO obtained in step (3) 3 The spherical HAP is dispersed in the solution, assisted by mechanical stirring during the hydrothermal reaction, and then centrifuged, washed and dried to obtain the spherical HAP.
[0006] Furthermore, in the water / ethylene glycol system, the ratio of water to ethylene glycol is 1:1 - 1:10.
[0007] Furthermore, the morphology control agent is polyvinyl pyrrolidone (PVP), and the concentration of the morphology control agent in the water / ethylene glycol system is 0.01-10 g / L.
[0008] Furthermore, the particle size control agent is one or more of sodium chloride, sodium nitrate, potassium chloride, potassium nitrate, and ammonium chloride, and the concentration of the particle size control agent in the water / ethylene glycol system is 0-10 M.
[0009] Furthermore, the soluble calcium salt is calcium chloride, calcium nitrate or a mixture of the two, and the calcium salt solution [Ca 2+ ] ion concentration is 0.01 - 2.0 M.
[0010] Furthermore, the soluble carbonate is one or more of sodium carbonate, potassium carbonate, and ammonium carbonate, and the carbonate solution [CO 32- ] ion concentration is 0.01 - 2.0 M.
[0011] Furthermore, in step (2), the calcium salt solution [Ca 2+ ] ion concentration and the [CO 3 2- ]The ion concentration is 1:1-1.1, so that the calcium salt can react fully.
[0012] Furthermore, in step (3), the stirring temperature is 15 - 90°C, the stirring speed is 200 - 900 rpm, the pumping time is 1 - 10 min, and the stirring time is 10 - 120 min.
[0013] Furthermore, in step (3), the centrifugation speed is 3000 - 9000 rpm, and the centrifugation time is 5 - 30 min.
[0014] Furthermore, the soluble phosphate is one or more of soluble orthophosphate, soluble monohydrogenphosphate, and soluble dihydrogenphosphate, and the phosphate solution [PO 4 3- ] ion concentration is 0.01 - 0.10 M.
[0015] Furthermore, the alkaline environment in step (4) is created by sodium hydroxide or ammonia water, and the pH range of the environment is 10-14.
[0016] Furthermore, in step (4), the spherical CaCO 3 The dosage is 0.01 - 0.20 M.
[0017] Furthermore, in step (4), the mechanical stirring speed during the hydrothermal reaction is 60-200 rpm, the hydrothermal reaction temperature is 80-200°C, and the hydrothermal reaction time is 6-36 h.
[0018] Furthermore, in step (4), the centrifugation speed is 3000 - 9000 rpm, and the centrifugation time is 5 - 30 min.
[0019] Furthermore, in step (4), the washing liquid is ultrapure water and ethanol.
[0020] Furthermore, in step (4), the spherical HAP is dried at a temperature of 50 - 100°C and a drying time of 2 - 24 h.
[0021] Compared with the prior art, the advantages of the present invention are: (1) The spherical HAP prepared in the present invention has good spherical morphology and dispersibility, high crystallinity, and the particle size can be controllably adjusted between 300 and 1600 nm.
[0022] (2) In the present invention, since the calcium salt solution and the carbonate solution contain an equal amount of morphology control agent, the influence of the concentration change of the morphology control agent on the crystal growth during the mixing process is avoided; ethylene glycol in CaCO 3 The protective film formed on the surface prevents the crystal from changing from spherical to square; the particle size control agent affects the Ca 2+ and CO 3 2- activity, thereby reducing the effective collision between ions and achieving CaCO 3 Controllable modulation of crystal size.
[0023] (3) The method provided by the present invention can simultaneously produce spherical HAP and spherical CaCO 3 The two high-value products have flexible process control and significant social and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 1 is a scanning electron microscope (SEM) image of the HAP prepared in Example 1, and A and B are only drawings at different magnifications.
[0026] Figure 2 is the X-ray powder diffraction (XRD) pattern of HAP prepared in Example 2.
[0027] Figure 3 This is the infrared absorption spectrum (FTIR) of the HAP prepared in Example 2.
[0028] Figure 4 1 is a SEM image of the HAP prepared in Example 3, and A and B are only drawings at different magnifications.
[0029] Figure 5 1 is a SEM image of the HAP prepared in Example 4, and A and B are only drawings at different magnifications.
[0030] Figure 6 1 is a SEM image of the HAP prepared in Example 5, and A and B are only drawings at different magnifications.
[0031] Figure 7 is the XRD pattern of HAP prepared in Example 6.
[0032] Figure 8 is a SEM image of the HAP prepared in Example 7. DETAILED DESCRIPTION
[0033] The present invention is described in detail below with reference to specific embodiments.
[0034] Example 1 2 L of water and 10 L of ethylene glycol were mixed at a ratio of 1:5, and 30 g of morphology control agent PVP and 0.3 M of particle size control agent sodium chloride were dissolved therein to form a water / ethylene glycol system. The obtained 12 L of water / ethylene glycol solution was divided into two portions, and 4 mol of calcium chloride and 4 mol of sodium carbonate were dissolved respectively. At 40 ° C, the sodium carbonate solution was stirred at 400 rpm, and the calcium chloride solution was pumped into the sodium carbonate solution at a speed of 600 mL / min. After the two solutions were completely mixed, the reaction continued for 50 min. After the reaction was completed, centrifuged at 8000 rpm for 6 min, washed and dried to obtain spherical CaCO 3 Dissolve 100 g of potassium dihydrogen phosphate in 10 L of water, adjust the pH to 13 with sodium hydroxide, and add 120 g of synthetic spherical CaCO 3 , hydrothermal reaction at 180℃ for 8 h, mechanical stirring at 100 rpm. After the reaction, centrifugation was performed at 8000 rpm for 6 min, washed with ultrapure water and ethanol, and dried at 100℃ for 6 h to obtain spherical HAP. Figure 1 SEM analysis showed that the synthesized HAP had a regular morphology, good dispersion, and a particle size of about 1300 nm.
[0035] Example 2 100 mL of water and 700 mL of ethylene glycol were mixed at a ratio of 1:7, and 1 g of morphology control agent PVP and 6 M of particle size control agent sodium nitrate were dissolved therein to form a water / ethylene glycol system. The obtained 800 mL of water / ethylene glycol solution was divided into two portions, and 0.5 mol of calcium nitrate and 0.5 mol of ammonium carbonate were dissolved respectively. At 26°C, the ammonium carbonate solution was stirred at 500 rpm, and the calcium nitrate solution was pumped into the ammonium carbonate solution at a speed of 150 mL / min. After the two solutions were completely mixed, the reaction continued for 25 min. After the reaction was completed, centrifuged at 8500 rpm for 10 min, washed and dried to obtain spherical CaCO 3 5 g of diammonium hydrogen phosphate was dissolved in 150 mL of water, the pH was adjusted to 11 with aqueous ammonia, and 6.5 g of the synthesized spherical CaCO was added. 3, hydrothermal reaction at 150℃ for 12 h, mechanical stirring at 60 rpm. After the reaction, centrifugation was performed at 8500 rpm for 10 min, washed with ultrapure water and ethanol, and dried at 60℃ for 24 h to obtain spherical HAP. XRD results are as follows Figure 2 As shown, it complies with the provisions of the HAP standard card. Figure 3 FTIR showed that the product had a peak at 629 cm -1 The hydroxyl absorption peaks at 561, 599, 960, 1015 and 1088 cm -1 The phosphate absorption peak is 1455 cm -1 The carbonate absorption peak is not visible, and there is no carbonyl, amino or other impurity peak, which is consistent with the FTIR spectrum characteristics of carbonated HAP.
[0036] Example 3 After dissolving 5 g of morphology control agent PVP in 2 L of water, two portions were prepared, each dissolving 4 mol of calcium chloride and 4 mol of sodium carbonate. The sodium carbonate solution was stirred at 400 rpm at 40°C, and the calcium chloride solution was pumped into the sodium carbonate solution at a rate of 100 mL / min. After the two solutions were completely mixed, the reaction was continued for 50 min. The remaining steps were the same as in Example 1. The SEM of HAP was obtained as shown in FIG. Figure 4 As shown, the synthesized HAP has two morphologies: spherical and square. The stacking phenomenon is relatively serious and the particle size is about 2000 nm.
[0037] Example 4 The particle size control agent dosage in Example 1 was changed to 0, and other conditions remained unchanged to obtain SEM as shown in FIG. Figure 5 The synthesized HAP has a regular morphology, good dispersion, and a particle size of about 1600 nm.
[0038] Example 5 The particle size control agent sodium chloride dosage in Example 1 was changed to 5 M, and other conditions remained unchanged to obtain SEM as shown in FIG. Figure 6 The synthesized HAP has a regular morphology, good dispersion, and a particle size of about 550 nm.
[0039] Example 6 The mechanical stirring speed during the hydrothermal reaction in Example 1 was changed to 0, and other conditions remained unchanged, and the XRD results were as follows: Figure 7 As shown. This indicates that the product contains a large amount of CaCO 3 and some HAP, indicating that the reaction was not complete.
[0040] Example 7 The mechanical stirring speed during the hydrothermal reaction in Example 1 was changed to 600 rpm, and other conditions remained unchanged to obtain SEM as shown in FIG. Figure 8 As shown, the synthesized HAP is in the form of needle-shaped aggregates, without spheres.
[0041] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A method for synthesizing spherical hydroxyapatite with controllable particle size, characterized in that: The method comprises the following steps: (1) Mixing water and ethylene glycol in proportion, and dissolving a morphology control agent and a particle size control agent therein to form a water / ethylene glycol system; (2) The water / ethylene glycol system obtained in step (1) is divided into two parts, and a soluble calcium salt is dissolved therein to form a calcium salt solution, and a soluble carbonate is dissolved therein to form a carbonate solution; (3) stirring and heating the carbonate solution obtained in step (2), pumping the heated and stirred calcium salt solution into the carbonate solution, reacting for a period of time, centrifuging, washing, and drying to obtain spherical calcium carbonate; (4) dissolving a soluble phosphate in water to obtain a phosphate solution, adjusting the pH to alkaline, dispersing the spherical calcium carbonate obtained in step (3) in the solution, performing a hydrothermal reaction with mechanical stirring, and then centrifuging, washing, and drying to obtain spherical hydroxyapatite.
2. The method for synthesizing spherical hydroxyapatite with controllable particle size according to claim 1, characterized in that: In the water / ethylene glycol system, the ratio of water to ethylene glycol is 1:1 - 1:10; the morphology control agent includes polyvinyl pyrrolidone, and the concentration of the morphology control agent in the water / ethylene glycol system is 0.01 - 10 g / L.
3. The method for synthesizing spherical hydroxyapatite with controllable particle size according to claim 1, characterized in that: The particle size control agent includes one or more of sodium chloride, sodium nitrate, potassium chloride, potassium nitrate, and ammonium chloride. The concentration of the particle size control agent in the water / ethylene glycol system is 0.01-10 M. The soluble calcium salt is calcium chloride, calcium nitrate, or a mixture of the two. The calcium salt solution [Ca 2+ ] ion concentration is 0.01 - 2.0 M.
4. The method for synthesizing spherical hydroxyapatite with controllable particle size according to claim 1, characterized in that: The soluble carbonate is one or more of sodium carbonate, potassium carbonate and ammonium carbonate. The carbonate solution contains [CO3 2- ] ion concentration is 0.01 - 2.0 M.
5. The method for synthesizing spherical hydroxyapatite with controllable particle size according to claim 1, characterized in that: In step (3), the stirring temperature is 15 - 90°C, the stirring speed is 200 - 900 rpm, the pumping time is 1 - 10 min, and the stirring time is 10 - 120 min.
6. The method for synthesizing spherical hydroxyapatite with controllable particle size according to claim 1, characterized in that: The soluble phosphate is one or more of soluble orthophosphate, soluble monohydrogenphosphate, and soluble dihydrogenphosphate. The phosphate solution contains [PO4 3- ] ion concentration is 0.01 - 0.10 M.
7. The method for synthesizing spherical hydroxyapatite with controllable particle size according to claim 1, characterized in that: The pH value is adjusted to alkaline in step (4) by using sodium hydroxide or ammonia water to adjust the pH to 10-14; the dosage of spherical calcium carbonate is 0.01-0.20 M.
8. The method for synthesizing spherical hydroxyapatite with controllable particle size according to claim 1, characterized in that: During the hydrothermal reaction in step (4), the mechanical stirring speed is 60 - 200 rpm, the hydrothermal reaction temperature is 80 - 200°C, and the hydrothermal reaction time is 6 - 36 h.
Citation Information
Patent Citations
A method for synthesizing spherical hydroxyapatite nanoparticles
CN110078037B
A method for preparing strontium-containing spherical hydroxyapatite
CN111115603B